2004
DOI: 10.1007/s00221-003-1781-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of muscle pain on elbow flexion and coactivation tasks

Abstract: The effects of muscle pain on movement can easily be observed in daily life routines. However, the influence of muscle pain on motor control strategies has not been fully clarified. In this human experimental study it was hypothesized that muscle pain affects the motor control of elbow flexion movements, in different combinations of range of motion and target size, by decreased agonistic muscle activity and increased antagonistic muscle activity with consequent implications on kinematic parameters. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 23 publications
2
31
2
Order By: Relevance
“…11,[24][25][26][27] Although the Pain Adaptation Model was developed for human chronic pain, it is interesting to note that the model would predict increases in one but not both muscle groups in this experimental rat model. Furthermore, findings from human studies of the effects of pain on locomotor, 44 trunk, 23 or forelimb 48,49 muscle activity are also not always consistent with the Pain Adaptation Model. For example, many inconsistencies have recently been identified in the literature on the relation between chronic low-back pain and muscle activity, 23 and neither the Vicious Cycle Theory nor the Pain Adaptation Model adequately predicted the effects of back pain on trunk muscle activation.…”
Section: Supporting Evidence For the Pain Adaptation Modelmentioning
confidence: 86%
See 1 more Smart Citation
“…11,[24][25][26][27] Although the Pain Adaptation Model was developed for human chronic pain, it is interesting to note that the model would predict increases in one but not both muscle groups in this experimental rat model. Furthermore, findings from human studies of the effects of pain on locomotor, 44 trunk, 23 or forelimb 48,49 muscle activity are also not always consistent with the Pain Adaptation Model. For example, many inconsistencies have recently been identified in the literature on the relation between chronic low-back pain and muscle activity, 23 and neither the Vicious Cycle Theory nor the Pain Adaptation Model adequately predicted the effects of back pain on trunk muscle activation.…”
Section: Supporting Evidence For the Pain Adaptation Modelmentioning
confidence: 86%
“…55 It is possible, however, in some individuals, these changes in muscle activity could lead to further pain, injury and disability for reasons that have yet to be elucidated. 23,35,49,[56][57][58][59][60][61][62] This raises the possibility that the Integrated Pain Adaptation Model reflects, in one sense, a unification of components of the Vicious Cycle Theory and the Pain Adaptation Model.…”
Section: Supporting Evidence For the Pain Adaptation Modelmentioning
confidence: 99%
“…Delayed reaction time has been found after musculoskeletal injuries (Taimela and Kujala 1992). Experimental (Madeleine et al 1999b;Ervilha et al 2004) and clinical (Radebold et al 2000(Radebold et al , 2001Hodges 2001) studies have shown that the reaction time is systematically prolonged during acute and chronic pain conditions. Moreover, Luoto et al (1998) showed that the severity of low-back pain is associated with longer reaction times.…”
Section: Kinematic Parametersmentioning
confidence: 96%
“…Finally, Birch et al (2000) concluded that experimental muscle pain had no effect on work performance when using a computer mouse but did modulate muscle activity during a low-precision task while no effect was found during high-precision task. In line, experimentally induced muscle pain did not change the overall EMG activity during high-precision elbow-joint movements but caused EMG activity changes in the overall muscle activity and in the initial EMG burst during low-precision tasks, which suggests changes in the motor planning (Ervilha et al 2004). Thus, it is clear that the motor strategy is disturbed by muscle pain.…”
Section: Introductionmentioning
confidence: 95%
“…Figure 1 shows the position of the participants before and after the elbow extension movement. The participants performed 10 trials (Ervilha and Arendt-Nielsen, 2004) in two movement conditions (impact and pointing movements), and trials of different instructions were executed with a random order. The instructions to the participants were: (i) "punch the target as quickly as possible", and (ii) "move your fist to the target as quickly and accurately as possible.…”
Section: Methodsmentioning
confidence: 99%